Workshop and Implementation of Adaptive Mathematics Learning Using the Interactive Mathway Application for Students with Learning Difficulties - Sofyan, Deddy; Putri, Kamelia Tri Nur; Pratiwi, Listiana Ayu; Apriliani, Yosi Khosilma (Indonesian Journal of Community Empowerment (IJCE), 2024)
This community service activity aims to enhance teachers’ ability to design and implement adaptive mathematics learning for students with learning difficulties through the use of the interactive Mathway application. The descriptive method was applied, including workshops, guidance, and hands-on practice using the application in planning and conducting learning activities. Observations indicate that teachers were able to adjust content, methods, and assessments according to students’ needs, making learning more engaging, interactive, and supportive of deeper understanding of mathematical concepts. This program is expected to strengthen teachers’ competencies in addressing diverse student abilities and to improve students’ motivation and mathematics learning outcomes, particularly for those experiencing learning difficulties.